A look at the past to draw lessons for the future: how the case of an urgent ICU transfer taught us to always be ready with a plan B - Brunelli, Laura; Miotto, Edoardo; Del Pin, Massimo; Celotto, Daniele; Moccia, Adriana; Borghi, Gianni; De Monte, Amato; Macor, Cristiana; Cocconi, Roberto; Lattuada, Luca; Brusaferro, Silvio; Arnoldo, Luca (Frontiers in Medicine, 2023)
Objective. The urgent transfer of an intensive care unit (ICU) is particularly challenging because it carries a high clinical and infectious risk and is a critical node in a hospital's patient flow. In early 2017, exceptional rainfall damaged the roof of the tertiary hospital in Udine, necessitating the relocation of one of the three ICUs for six months. We decided to assess the impact of this transfer on quality and patient safety using a set of indicators, primarily considering the incidence of healthcare-associated infections (HAIs) and mortality rates. Methods. We performed a retrospective, observational analysis of structural, process, and outcome indicators comparing the pre-and posttransfer phases. Specifically, we analyzed data between July 2016 and June 2017 for the transferred ICU and examined mortality and the incidence of HAI. Results. Despite significant changes in structural and organizational aspects of the unit, no differences in mortality rates or cumulative incidence of HAIs were observed before/after transfer. We collected data for all 393 patients (133 women, 260 men) admitted to the ICU before (49.4%) and after transfer (50.6%).The mortality rate for 100 days in the ICU was 1.90 (34/1791) before and 2.88 (37/1258) after transfer (p=0.063). The evaluation of the occurrence of at least one HAI included 304 patients (102 women and 202 men), as 89 of them were excluded due to a length of stay in the ICU of less than 48 hours; again, there was no statistical difference between the two cumulative incidences (13.1% vs 6.9%, p=0.075). Conclusions. In the case studied, no adverse effects on patient outcomes were observed after urgent transfer of the injured ICU. The indicators used in this study may be an initial suggestion for further discussion.